Cognitive flexibility, central coherence, and quality of life in anorexia nervosa - Brockmeyer, Timo; Febry, Hagen; Leiteritz-Rausch, Anna; Wünsch-Leiteritz, Wally; Leiteritz, Andreas; Friederich, Hans-Christoph (Journal of eating disorders, 2022)
Anorexia nervosa (AN) has consistently been found to be associated with poor cognitive flexibility and central coherence. These two cognitive functions have been considered important maintenance factors in AN and are addressed by specific treatment approaches such as cognitive remediation therapy. While there is clear empirical evidence that difficulties in such cognitive functions are related to impaired daily functioning in schizophrenia and bipolar disorder, this potential association has received only little attention in AN research so far. Therefore, the aim of this study was to examine potential relationships between weak cognitive flexibility, central coherence, and poor quality of life (QoL) in AN.
Gesehen am 17.03.2022